Category Shifts and Impact of Translation in “The Secret of Unicorn” Movie Texts - Seftiy Andriyaniy; Yunita Widiyantari (Faculty of Language and Literature, University of Surakarta, 2020)
This study aims for (1) analyzing the kinds of category shifts found in the movie of The Adventure of Tintin “The Secret of Unicorn” into Indonesian Subtitle, (2) explaining the dominant category, and (3) describing the influences of those category shifts on transferring the messages of the source language. The data in this research were all of the sentences spoken by the actors in The Adventure of Tintin “The Secret of Unicorn“ movie, whose translations (subtitles) contain any type of category shifts This research was a descriptive qualitative research. The process of collecting data is by taking all data that are suitable to the criteria and supported the research. There are four types of category shifts occured in the subtitling text of the The Adventure of Tintin “The Secret of Unicorn” movie. They are structure shift, class shift, unit shift and intra-system shift. The structure shift has the highest frequency, that is 289 cases or about 50.7 %. The occurrence of category shift in this movie can make the translation’s result more natural, accurate, and communicative.